Knowledge management challenges in an alliance-based major project delivery organisation. Issue 1 (31st December 2022) - Howe, Stephen
ABSTRACT: The Level Crossing Removal Project (LXRP) is using a Program alliance-based delivery model to achieve 75 level crossing removals by 2025. The systems and knowledge required have developed iteratively, as LXRP and its delivery partners have adjusted to lessons learned and responded to opportunities for improvement. This paper focuses on the knowledge management challenges faced to date on the LXRP 'client-side'. It presents a case study on emerging solutions to these challenges and examines several subtopics including systems, data types, data management practices and the differing data needs across diverse areas within engineering and associated disciplines. It also examines end of project record archiving issues in a major project alliance delivery model context, and how the needs of different project stakeholders may differ and create challenges for the project owner's representative. Recommendations for project owners and for further research are provided in conclusion.